ANALISIS KOMPETENSI SUMBER DAYA MANUSIA PADA INSPEKTORAT WILAYAH KABUPATEN KUTAI TIMUR - Maisyarah, Syarifah (PREDIKSI, 2016)
This study aims to know and describe the competence of human resources in the Regional Inspectorate East Kutai. This study uses qualitative descriptive approach.The results showed that based on the analysis of data using the value of the average percentage of the level of competence of employees amounted to 85.02%. This means that the Employee Competence in East Kutai Regional Inspectorate included in the interval 76% - 100% or fit in either category.Â